2021
DOI: 10.1093/bjs/znab152
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of robotic distal and total gastrectomy

Abstract: Background This study aims to assess the learning curve of robotic distal gastrectomy (RDG) and robotic total gastrectomy (RTG) for gastric cancer. Methods Data on consecutive patients who underwent robotic gastrectomy for gastric cancer by five surgeons between March 2010 and August 2019 at two high-volume institutions were collected. The learning curve was determined based on the analyses of operation time and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Our reported learning curve is similar to other fields of surgery when comparing the impact of experience to operative time and complication rate, the two most commonly measured variables for learning curves. Our finding of decreased mean operative time is consistent with findings from several other studies 9,18–22 . While the measured complications are different, several studies in other surgical fields have demonstrated a decrease in individual and overall complication rates with experience 18,21,23,24 …”
Section: Discussionsupporting
confidence: 91%
“…Our reported learning curve is similar to other fields of surgery when comparing the impact of experience to operative time and complication rate, the two most commonly measured variables for learning curves. Our finding of decreased mean operative time is consistent with findings from several other studies 9,18–22 . While the measured complications are different, several studies in other surgical fields have demonstrated a decrease in individual and overall complication rates with experience 18,21,23,24 …”
Section: Discussionsupporting
confidence: 91%
“…The turning point in the learning curve of RG was reportedly considered to be around 18 to 25 cases; the complication rate and conversion rate up to the turning point were signi cantly higher than those afterwards [12][13][14]. In other words, the technical immaturity of endoscopic surgeons has a signi cant impact on the surgical outcome of RG.…”
Section: Discussionmentioning
confidence: 99%
“…However, robot-speci c aspects such as port placement, docking maneuvers, the master controller and foot pedals on the surgeons' console, and the lack of haptic feedback are all crucial for surgeons to master in their training [11]. The learning curve for RG is reportedly less steep compared to traditional laparoscopic surgery, but there may have been bias since these studies were conducted on endoscopic surgeons with prior experience in conventional LG [12][13][14]. Nevertheless, with the increasingly widespread use of surgical robots, the number of surgeons performing RG for gastric cancer are expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RA-CUSUM analysis was applied to depict the success or failure of the TLAP technique. First, baseline variables with P < 0.20 in the univariate association were considered for inclusion, and the predicted probabilities of each case were calculated according to the regression coefficients of the variables in the final multivariate regression model ( 20 ). Then, for each failure case, the RA-CUSUM value was incremented by (1-predicted probability of failure).…”
Section: Methodsmentioning
confidence: 99%